SURFACE CHARACTERISTICS HRS (HOT ROLLED SHEET) FILLER BASE USING FLY-ASH, BOTTOM ASH, CEMENT AND ABU STONE - Radi Tyo; Yasruddin Yasruddin (Universitas Lambung Mangkurat, 2017)
The results showed that the stability of Marshall on a combination of filler (Fly-ash, bottom ash, cement,dust stone) all mixtures meet the specifications from Bina Marga is 800 kg. Flow on a combination of filler (Fly-ash, bottom ash, cement,dust stone) all mixtures meet the specifications from Bina Marga is 3 mm. VFB on a combination of filler (Fly-ash, bottom ash, cement,dust stone) all mixtures meet the specifications from Bina Marga is 68%. VIM on a combination of filler (Fly-ash, bottom ash, cement,dust stone) all mixtures meet the specifications from Bina Marga is 4-6% except filler Fly-Ash (3.6%) and bottom ash (3%) did not meet specifications. VMA on a combination of filler (Fly-ash, bottom ash, cement,dust stone) all mixtures meet the specifications from Bina Marga 17%. MQ on a combination of filler (Fly-ash, bottom ash, cement,dust Stone) all mixtures meet the specifications From Bina Marga is 250 kg / mm. So we get the rest of the stability index immersion with combination All filler meets the specifications from Bina Marga is 90%. A mixture of filler that can be used as road pavement materials standard specifications from Bina Marga (2010) is cement and dust Stone.